Inovasi Produk Olahan Jamur Tiram (Pleurotus ostreatus) Berupa Jamur Krispi Di Desa Kelidang Atas - Syaputra, Falius Bahri; Deri, Deri; Rosianti, Elpera (Jurnal Dehasen Mengabdi, 2024)
Every main commodity owned by a village should be developed so that it becomes a superior commodity with further manufactured products to increase the selling value of these commodities so that the echoes of the Superior Commodity-Based Village program do not only become discourse, but can be realized not only by villagers but all elements of society. including academic intellectuals such as lecturers and students. At the Student Community Service (PMM) the Faculty of Agriculture team conducted outreach to villagers regarding packaging, as well as calculating HPP from SJM as a red ginger processed product to increase the selling value of red ginger as a potential commodity from Kelindang Atas Village.